A barrier analysis for distributed recycling of 3D printing waste: Taking the maker movement perspective. (20th December 2019) - Peeters, Bob; Kiratli, Nadine; Semeijn, Janjaap
Abstract: The democratization of manufacturing, led by personal fabrication tools such as three-dimensional (3D) printers, demands evaluations of the sustainability of such practices. To demonstrate the circular economy potential of personal fabrication through 3D printing (3DP), this study seeks a better understanding of the barriers to distributed recycling of 3DP waste in a maker movement context. Interviews with those involved in the maker movement and related potential stakeholders reveal barriers that hinder local recycling of 3DP waste. An interpretive structural modeling (ISM) method clarifies the structures of the relationships among the barriers, to identify the most cumbersome ones that hinder the local recycling of 3DP waste. The findings provide academics and practitioners with deeper insights into the barriers to distributed recycling of 3DP waste, as well as ideas for accelerating innovative 3DP solutions for sustainability. Highlights: Applying ISM identifies 22 barriers to distributed recycling of 3DP waste. The barriers are technical, economic, social, organizational, and regulatory in nature. Quality demands from consumers and consumption behaviors constitute important barriers. Homogeneous waste streams and avoiding contamination are key to encouraging 3DP recycling in makerspaces. Overcoming barriers requires concerted effort by varied stakeholders: legislative bodies, companies, makerspaces, consumers.